Implementasi Prinsip Kehati-hatian dalam Sanitary and Phythosanitary Agreemant, Studi Kasus: Keputusan Appellate Body WTO dalam Kasus Hormone Beef antara Uni Eropa dengan Amerika Serikat - Sri Wartini (Jurnal Hukum IUS QUIA IUSTUM, 2007)
The implementation of precautionary principle on the the decision of Appellate Body WTO on the case of Hormone Beef between European Union and United State based on the framework of SPS Agreement. The precautionary principle is only implicitly regulates   on the SPS Agreement. The Appellate Body has not yet adopted the precautionary principle as customary international law.